Assembling a multi-component and multifunctional integrated filament scaffold based on triaxial 3D bioprinting technology. (November 2022) - Wu, Tingbin; Huang, Qiwei; Lai, Simin; Yu, Hui
Abstract: Currently, most scaffolds produced by 3D printing is based on a single material which limits their wide application in the medical field. In this study, a multi-component and multifunctional shell-core filament 3D scaffold was designed and subsequently produced by triaxial bioprinting technology using sodium alginate, gelatin, collagen, chitosan and platelet-rich plasma (PRP) as biological raw materials. The resulting filamentous 3D scaffold exhibited excellent water absorption and retention capacity, good biocompatibility as well as antibacterial effects. In addition, compared with clinically-used PRP-gel, the filamentous 3D stent could effectively reduce the frequency of PRP administration by 50–75% during wound treatment while also showing better therapeutic effects. Graphical abstract: Image 1 Highlights: Multiple biomaterials were integrated into one body by triaxial 3D bioprinting technology to prepare multifunctional 3D scaffold materials. The 3D scaffolds had good biocompatibility, excellent water absorption and retention as well as antibacterial properties, while promoting the adhesion, migration and proliferation of L929 cells. The multifunctional 3D scaffolds exhibited better chronic wound healing properties than clinical PRP-gels, with a 50–75% reduction in the frequency of PRP-gel administrations.